Comparison on Bioactivities and Characteristics of Polysaccharides From Four Varieties of Gastrodia elata Blume - Ji, Ning; Liu, Peng; Zhang, Ni; Yang, Shengyan; Zhang, Mingsheng (Frontiers in Chemistry, 2022)
The composition, physicochemical properties, in vitro biological activity, and hypoglycemic activity exhibited by polysaccharides from four varieties of G. elata were investigated in this study; the four extracted GaE polysaccharides were termed as GaE-B (G. elata Bl. f. glauca S. chow polysaccharides), GaE-R (G. elata Bl. f. elata polysaccharides), GaE-Hyb (hybridization of G. elata Bl. f. glauca S. chow and G. elata Bl. f. elata polysaccharides), and GaE-G (G. elata Bl. f. viridis Makino polysaccharides). As revealed by the results, the GaE polysaccharides were found with the same monosaccharide composition, primarily including glucose, whereas the content of each variety was significantly different. In addition, different degrees of differences were found in the in vitro antioxidant and hypoglycemic activity, molecular weight, yield, and chemical composition exhibited by the abovementioned varieties. However, GaE-B and GaE-Hyb were found with similar physical properties, chemical composition, and antioxidant and hypoglycemic activity. GaE-R had the lowest yield, total sugar content, and molecular weight, whereas it involved higher xylose, binding protein, and polyphenols as well as higher antioxidant and hypoglycemic activity. In contrast, GaE-G was found with the highest yield, total sugar content, and molecular weight, whereas it contained the lowest xylose, binding protein, and polyphenols, as well as the weakest antioxidant and hypoglycemic activity. In brief, the polysaccharide of G. elata, a plant resource for homology of medicine and food, could more significantly enhance the biological activity of G. elata as it was released in the process of decocting and stewing. To be specific, the assessment of polysaccharide activity alone suggested that GaE-R was the best.